Case Report: Zolpidem’s paradoxical restorative action: A case report of functional brain imaging - Boisgontier, Jennifer; Beccaria, Kévin; Saitovitch, Ana; Blauwblomme, Thomas; Guida, Lelio; Fillon, Ludovic; Dufour, Christelle; Grill, Jacques; Lemaitre, Hervé; Puget, Stéphanie; Vinçon-Leite, Alice; Dangouloff-Ros, Volodia; et al. (Frontiers in Neuroscience, 2023)
Zolpidem is a sedative drug that has been shown to induce a paradoxical effect, restoring brain function in wide range of neurological disorders. The underlying functional mechanism of the effect of zolpidem in the brain in clinical improvement is still poorly understood. Thus, we aimed to investigate rest brain function to study zolpidem-induced symptom improvement in a patient who developed postoperative pediatric cerebellar mutism syndrome, a postoperative complication characterized by delayed onset transient mutism/reduced speech that can occur after medulloblastoma resection. The patient experienced clinical recovery after a single dose of zolpidem. Brain function was investigated using arterial spin labeling MRI and resting-state functional MRI. Imaging was performed at three time-points: preoperative, postoperative during symptoms, and after zolpidem intake when the symptoms regressed. Whole brain rest cerebral blood flow (CBF) and resting state functional connectivity using Pearson coefficient correlations between pairs of regions of interest were investigated two-by-two at the different time points. A comparison between postoperative and preoperative images showed a significant decrease in rest CBF in the left supplementary motor area, Broca’s area, and the left striatum and a decrease in functional connectivity within the dentato-thalamo-cortical and cortico-striato-pallido-thalamo-cortical loops. Post-zolpidem images showed increased CBF in the left striatum and increased functional connectivity within the disrupted loops relative to postoperative images. Thus, we observed functional changes within the broader speech network and thalamo-subcortical interactions associated with the paradoxical effect of zolpidem in promoting clinical recovery. This should encourage further functional investigations in the brain to better understand the mechanism of zolpidem in neurological recovery.